Juncus in Northern Patagonian Wetlands - Jocou, Adriel Ian (2022)
Juncus is the most species-rich genus of Juncaceae in northern Patagonian wetlands. Therefore, the correct identification of Juncus taxa is crucial in floristic studies of the region’s wetlands. Since Juncus is taxonomically complicated and it has not been revised in Argentina, the objective of this work is to review the taxa that occur in northern Patagonian wetlands. We provide a key, morphological and ecological information, and photographs of each taxon. Eight species and nine infraspecific taxa of Juncus grow in the northern Patagonian wetlands, where they are found under a number of different water and soil conditions. Juncus stipulatus is excluded for the northern Patagonian wetlands, because it was previously recorded based on a misidentification.